PERBANDINGAN MODEL POLA PENGELOLAAN KEUANGAN PERGURUAN TINGGI NEGERI - Hermawan Rudhianto; Tri Utami; Wahyu Widarjo (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
One of the country’s aim as it is written in 1945 Constitution is to develop the nation’s intellectual life. In order to deliver those aim, the role of state university (PTN) is highly needed. PTN is established by the government. The PTN’s management pattern status is heterogeneous and it depend on its independence. The higher its autonomy, the higher its independence. This research was conducted to get knowledge about the difference of PTN finance management. The results of this research are expected as a guide for PTN which will switch its status from work unit to Public Service Agency (BLU) and from BLU to State Higher Education Institution of Incorporated Legal Entity (PTN-BH), even from work unit to PTN-BH. Furthermore, it can also be used for university leader basis decision making. This research applied a qualitative research with exploratory analysis level. The data were collected through observation, deep interview, Focus Group Discussion (FGD) and documentation delivered to 31 PTN with work unit, BLU and PTN-BH financial management pattern. The result of this research demonstrates the difference of financial management pattern among PTN with common work unit, BLU work unit and PTN-BH according to its autonomy level. The difference of financial management pattern can be seen through conclusion part in this research.